Case report and review of literature: incisional site metastasis in patient with carcinoma cervix - Gupta, Sangeeta; Gupta, Taru; Kaur, Parminder; Jain, Manish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Metastasis to skin occurs rarely in gynaecological malignancies especially in carcinoma cervix. Cervical malignancy mainly metastasizes to the pelvis, lungs, bones, and liver. Metastasis to the skin is an unusual presentation during the course of carcinoma of the cervix, even in terminal stages of disease. The prognosis after skin metastasis is poor and often a terminal presentation. We report a case of a patient who underwent total abdominal hysterectomy with bilateral salpingo-oophorectomy for postmenopausal bleeding without preoperative evaluation in a private enterprise in 2012 and carcinoma cervix (squamous cell carcinoma) was detected on histopathology. For the same, she received chemoradiation at an Oncocentre. Twenty two months after surgery she developed recurrence on abdominal scar site. At PGIMSR Basaidarapur she underwent wide local excision of anterior abdominal wall with tensor fascia lata flap elevation. Presently she is under follow-up and planned for chemotherapy. To conclude, incisional cutaneous metastasis is a rarity with carcinoma cervix and is considered as an ominous prognostic sign with short survival after diagnosis.